Managing children: An insight into Malay parents' involvement in their children's learning - Hanafi, Zahyah; Yaakub, Noran Fauziah; Awang Hashim, Rosna (Universiti Utara Malaysia, 2002)
Socio-economic status not only influences family beliefs about values of education, but may affect how academic expectations are communicated by parents and perceived by their children. This study examined (1) the level of parental involvement (achievement values' interest in homework and discussion on school matters) among Malay parents, and (2) parental involvement and its relationship with academic achievement. Measures of parents' involvement were obtained from Malay boys (n=146) and girls (n =284), aged seventeen, 1iving with both biologica1 parents. Adolescents' perceptions of materna1 and paternal involvement at home were measured using Paternal and Maternal Parental Involvement Scale (Paulson, 1994b). Results indicated that Malay parents tend to emphasize more on achievement values, less on interest in homework and discussion on school matters. In terms of gender differences, there were significant differences between mothers' and fathers' involvement and these differences were-found to differ towards sons and daughters. Discussions and implications were outlined.